2019
DOI: 10.11628/ksppe.2019.22.4.333
|View full text |Cite
|
Sign up to set email alerts
|

Community Gardening Activities and Their Effects on Mental Health of Residents

Abstract: This study was conducted to find out the effects of plant cultivation activities in the village gardening program hosted by Gyeonggi-do on the psychology and physiology of participants. This study conducted a survey on 20 villagers aged 57.70±9.23 on average and collected their saliva before Session 1 and after the final Session 10. The experiment was conducted by carrying out the village gardening program once a week for total 10 weeks. Psychological assessment was conducted by measuring the level of plant cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Therefore, agroealing activities seem to reduce the concentration of salivary cortisol, a stress hormone. The result of Jang, Gim, et al (2019) that activities of maintaining a community garden and planting plants significantly reduced the total cortisol concentration of participants is similar to the result of this study that the agro-healing activities reduced the concentration of salivary cortisol, a stress hormone. In addition, the physical actions of agro-healing activities such as plowing the soil, sowing seeds, weeding out and watering plants (Matsuo and Miyajima, 1998) were reported to reduce depression or stress that participants experienced (J.Y.…”
Section: Changes In the Cortisol Level Of Participants After Participsupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, agroealing activities seem to reduce the concentration of salivary cortisol, a stress hormone. The result of Jang, Gim, et al (2019) that activities of maintaining a community garden and planting plants significantly reduced the total cortisol concentration of participants is similar to the result of this study that the agro-healing activities reduced the concentration of salivary cortisol, a stress hormone. In addition, the physical actions of agro-healing activities such as plowing the soil, sowing seeds, weeding out and watering plants (Matsuo and Miyajima, 1998) were reported to reduce depression or stress that participants experienced (J.Y.…”
Section: Changes In the Cortisol Level Of Participants After Participsupporting
confidence: 87%
“…In addition, the effects of the key variables of participants on their loyalty were analyzed, and the level of stress and satisfaction with services and the program were found to have a strong influence on loyalty. Jang, Gim, et al (2019) reported that the level of stress was lowered from the level of being likely to be developed into a mental illness before participating in the activity of maintaining a community garden to the level of having been already affected by stress after participating in the activity, and thus that the program comprised of plant cultivation activities was effective in reducing the level of stress that participants experienced. Jang et al (2018) also reported that the level of cortisol, a stress hormone, of parents of elementary school students was statistically significantly reduced after participating in plant cultivation activities, indicating that plant cultivation activities positively affect their healing effects.…”
Section: Effects Of Key Variables On Loyaltymentioning
confidence: 99%
“…These results were similar to those of the following earlier studies. Jang, Gim et al (2019) reported that the total concentration of cortisol after participating in community gardening activities including growing plants significantly decreased from the level before participating in the activities. Lee et al (2013) that provided a horticultural activity program for prisoners to be released reported that the control group did not show any statistically significant difference, but that the experimental group showed a statistically significant decrease in the level of depression and cortisol after participating in the program from the level before participating in the program.…”
Section: Changes In the Cortisol Level Of Participants After Agro-heamentioning
confidence: 99%
“…Studies of gardening and similar activities include: a systematic review of current research on the health benefits of a garden environment (Kang et al, 2020); a study on the effects of a horticultural therapy program focusing on gardening activities ; an analysis of the healing effects of forest therapy and horticultural therapy (Park et al, 2015); community gardening activities and their effects on mental health of residents (Jang et al, 2019). There has also been a study on the effect of garden healing programs on the psychological emotion of the bereaved (Na, 2020).…”
Section: Introductionmentioning
confidence: 99%